THEORETICAL AND LEGAL ASPECTS OF THE EFFECTIVENESS OF THE IMPLEMENTATION OF DISCIPLINARY PENALTIES IN LABOR LAW - Razieva, Динара Багдатовна; Yesenzholov , Нуролла Ергалиевич (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
The subject of the study is the actual problem of the effectiveness of disciplinary responsibility under the labor legislation of the Republic of Kazakhstan. The article attempts to conduct a theoretical and legal analysis of disciplinary penalties, due to the recognition of the indisputable importance of the theory of labor law in the development of fundamental ways of legal regulation of labor relations in the Republic of Kazakhstan. The authors, emphasizing the dependence of the effectiveness of the implementation of disciplinary penalties on the degree of achievement of the intended goal, critically evaluate the views of scientists on the punitive nature of disciplinary responsibility. The authors, highlighting the problem of the certainty of the subject composition of disciplinary responsibility, question the inclusion in paragraph 1 of Article 64 of the Labor Code of the Republic of Kazakhstan of the first head of the national management holding. Within the framework of the study, the system of disciplinary penalties applied to an employee in case of a disciplinary offense is analyzed, reasonable conclusions are made about the expediency of making amendments and additions to Article 64 of the Labor Code of the Republic of Kazakhstan and Article 22 of the Regulatory Resolution of the Supreme Court of the Republic of Kazakhstan "On certain issues of application of legislation by courts in resolving labor disputes". The authors reveal the contradictions of Article 66 of the Labor Code of the Republic of Kazakhstan and paragraph 17 of the Regulatory Resolution of the Supreme Court of the Republic of Kazakhstan "On certain issues of the application of legislation by courts in resolving labor disputes" in terms of calculating the terms of disciplinary penalties. The article highlights the problem of the absence in the labor legislation of a fixed mechanism for the commensurability of misconduct and penalties, on the basis of which it is proposed to make additions to Article 65 of the Labor Code of the Republic of Kazakhstan.